The election of Romani kings as an example of Romani self-organization in the interwar period - Hajská, Markéta (Romano džaniben, 2024)
The article addresses the institution of the Romani "king" and the processes of his election among the Roma in interwar Czechoslovakia. These activities are seen as manifestations of Romani self-organization and efforts to seek self-representation independent of the majority institutions. It is primarily based on texts from the contemporary press, although this source is tinged with a considerable amount of sensationalism and exoticization. The institution of the Romani king is presented on the example of neighbouring Poland, where the older tradition of electing Romani kings was revived in the interwar period by Kalderash boilermakers from the Kwiek family. The article focuses on activities of Czechoslovak Roma aiming at the election of their own king, involving different Romani communities from different parts of the country. It presents reports about Romani congresses and meetings organized with the aim of electing a king or taking a public position on another election. It also discusses the terminological adequacy of the Czech term "king" as a term established in non-Romani references to the position, but is not generally used in Romani.